Pengaruh Pergeseran Lempeng Bumi Terhadap Penentuan Arah Kiblat Masjid Agung Bait Al-Mu'minin Kabupaten Jombang - M. Ma’muri AS (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2016)
This study is based on many natural earthquakes due to shifting earth plates in Indonesia. Indonesia consists of three plates, namely the Australian plate, the Pacific plate and the Eurasian plate. Those becomes a problem if the earth's shifting plates change the position of Qiblat direction as a very strong earthquake occurred on May 27, 2006 in the area of ​​Yogyakarta so they felt in other areas such as in East Java, though very small. The earthquake was caused by the seduction of the Indo-Australian plate against the Eurasian plate. The purpose of this study was to determine how much influence the earth's shifting plates to determine the direction of Qiblat, as well as knowing the position of the Qiblat direction mosques, with the study site of the Great Mosque Bait al Mu'minin Jombang and several mosques around as the comparison. The research is qualitative-field research with direct measurement using the tools of the Shadow of the Sun (Stick istiwa’), Magnetic Compass, Compass Qiblat and Digital Theodolite supported by some books related to this research. The results show that the earth's shifting plates can affect a shift in the direction of Qiblat, but the effect is not significant. Earth every year shifted about 7 cm to change the arc: 00000'00.00